Liberdade vigiada: tutelas e órfãos em Pindamonhangaba/SP (1888-1892) - Castilho, Mateus Henrique Obristi (2018)
The object of study of this research is the comprehension of the work’s sphere in Pindamonhangaba society, located in Paraíba Valley, by the analysis of the exploitation of the work of under aged, of the ingenuos and unprotected orphan, children of former slaves, released and poor single women was widely spreaded between many farmers and elite members in the slavery end. When being tutores, such minors were directed to the work in farming or to the housework, from the consult of the tutelage’s documents processed in the judgment of orphans, from 1888 to 1892. High number of tutelage, starting in 1888 year, originates from legal precedent from Imperial Legislation in 1887 year, since judicial measure, allowed farmers to recrute the work of under aged and unprotect orphans, was assured by Aviso, N.34, on 24 October, Ministry of Justice, that then Justice Minister Samuel Wallace Mac-Dowell, recommended to judges of orphans to give farmers preference to receive under aged and under protected orphans and use their work. We started the study through the problematization of the recommendation from the 1887 year. Later, we followed the analysis of the historical sources of tutelage. Once more the black family was separated, this time by tutelage, so we stand out the fight of families in justice to have their relative. However, the fight was not limited to the justice, but also to the escape of children under guardianship